Analisis Perhitungan Cadangan Kerugian Penurunan Nilai PT. Bank BRI Agroniaga Tbk Cabang Pekanbaru Tahun 2016 - Jeli Nata Liyas (Universitas PGRI Madiun, 2018)
This study analyzes the calculation of fund formation Allowance for impairment losses according to banking rules and according to the tax rules. Allowance for impairment on an allowance is established when the carrying value after impairment are less than the carrying amount of the initial. Recognition of allowance for impairment in accordance with banking regulations by Indonesian Banking Accounting Guidelines , while according to the tax rules on the terms of Regulation of the Minister of Finance No.81/PMK.03/2009. Fiscal correction is used to adjust for differences in the recognition of allowance for impairment in accordance with banking rules and according to the rules of taxation. Analysis of the data used is quantitative descriptive analysis. The analysis showed that there was no difference according to the allowance for impairment recognition PT. Bank BRI Agroniaga, Tbk with banking rules. The same is shown in the application of fiscal correction to the allowance for impairment of PT. Bank BRI Agroniaga, Tbk accordance with the tax regulations. This means recognition of allowance for impairment of PT. Bank BRI Agroniaga, Tbk has appropriate banking regulation and taxation.